Hermite–Hadamard Inequalities for Harmonic s, m-Convex Functions. (26th September 2020) - Xu, Jian Zhong; Raza, Umar; Javed, Muhammad Waqas; Hussain, Zaryab
Abstract : The objective of this article is to establish some Hermite–Hadamard-type inequalities via harmonic s, m -convex functions in the framework of conformal fractional integral.